sEMG Activity in Superimposed Vibration on Suspended Supine Bridge and Hamstring Curl - Aguilera-Castells, Joan; Buscà, Bernat; Arboix-Alió, Jordi; Miró, Adrià; Fort-Vanmeerhaeghe, Azahara; Peña, Javier (Frontiers in Physiology, 2021)
Traditionally in strength and conditioning environments, vibration has been transmitted using platforms, barbells, dumbbells, or cables but not suspension devices. This study aimed to examine the effects on the lower limb of applying superimposed vibration on a suspension device. Twenty-one physically active men and women performed supine bridge and hamstring curl exercises in three suspended conditions (non-vibration, vibration at 25 Hz, and vibration at 40 Hz). In each exercise condition, the perceived exertion scale for resistance exercise (OMNI-Res) was registered, and the electromyographic signal was assessed for gastrocnemius (medialis and lateralis), biceps femoris, semitendinosus, gluteus maximus, and rectus femoris. A linear mixed model indicated a significant fixed effect for vibration at 25 Hz and 40 Hz on muscle activity in suspended supine bridge (p<0.05), but no effect for suspended hamstring curl (p>0.05). Likewise, Friedman test showed a significant main effect for vibration at 25 Hz and 40 Hz in suspended supine bridge (p<0.05) but not for suspended hamstring curl (p>0.05) on OMNI-Res. Post hoc analysis for suspended supine bridge with vibration at 25 Hz showed a significant activation increase in gastrocnemius lateralis (p = 0.008), gastrocnemius medialis (p = 0.000), semitendinosus (p = 0.003) activity, and for semitendinosus under 40 Hz condition (p = 0.001) compared to the non-vibration condition. Furthermore, OMNI-Res was significantly higher for the suspended supine bridge at 25 Hz (p = 0.003) and 40 Hz (p = 0.000) than for the non-vibration condition. Superimposed vibration at 25 Hz elicits a higher neuromuscular response during the suspended supine bridge, and the increase in vibration frequency also raises the OMNI-Res value.